Cyanobacteria Respond to Low Levels of Ethylene - Allen, Cidney J.; Lacey, Randy F.; Binder Bickford, Alixandri B.; Beshears, C. Payton; Gilmartin, Christopher J.; Binder, Brad M. (Frontiers in Plant Science, 2019)
Ethylene is a gas that has long been known to act as a plant hormone. We recently showed that a cyanobacterium, Synechocystis sp. PCC 6803 (Synechocystis) contains an ethylene receptor (SynEtr1) that regulates cell surface and extracellular components leading to altered phototaxis and biofilm formation. To determine whether other cyanobacteria respond to ethylene, we examined the effects of exogenous ethylene on phototaxis of the filamentous cyanobacterium, Geitlerinema sp. PCC 7105 (Geitlerinema). A search of the Geitlerinema genome suggests that two genes encode proteins that contain an ethylene binding domain and Geitlerinema cells have previously been shown to bind ethylene. We call these genes GeiEtr1 and GeiEtr2 and show that in air both are expressed. Treatment with ethylene decreases the abundance of GeiEtr1 transcripts. Treatment of Geitlerinema with 1000 nL L–1 ethylene affected the phototaxis response to white light as well as monochromatic red light, but not blue or green light. This is in contrast to Synechocystis where we previously found ethylene affected phototaxis to all three colors. We also demonstrate that application of ethylene down to 8 nL L–1 stimulates phototaxis of both cyanobacteria as well as biofilm formation of Synechocystis. We formerly demonstrated that the transcript levels of slr1214 and CsiR1 in Synechocystis are reduced by treatment with 1000 nL L–1 ethylene. Here we show that application of ethylene down to 1 nL L–1 causes a reduction in CsiR1 abundance. This is below the threshold for most ethylene responses documented in plants. By contrast, slr1214 is unaffected by this low level of ethylene and only shows a reduction in transcript abundance at the highest ethylene level used. Thus, cyanobacteria are very sensitive to ethylene. However, the dose-binding characteristics of ethylene binding to Geitlerinema and Synechocystis cells as well as to the ethylene binding domain of SynEtr1 heterologously expressed in yeast, are similar to what has been reported for plants and exogenously expressed ethylene receptors from plants. These data are consistent with a model where signal amplification is occurring at the level of the receptors.